UPAYA HUKUM PERLINDUNGAN KONSUMEN TERHADAP PENGGUNA JASA ANGKUTAN KERETA API DI INDONESIA - Rusmiyah Rusmiyah (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2022)
The focus of the problem in this writing is whether the provisions in Law Number 23 of 2007 concerning Railways (Railway Law) are effectively used as a basis for transportation responsibility and how is the transportation responsibility carried out by PT KAI (Persero) to consumers. The purpose of this study is to analyze the provisions in the Railway Law whether they are effectively used as a basis for transportation responsibility and to determine the responsibility of transportation carried out by PT KAI (Persero) to consumers. This research method is a type of normative-empirical legal research using two approaches, namely the statute approach and the case approach, as well as through primary data and secondary data, while data analysis is carried out qualitatively-prescriptively. The results of this study show that the provisions in the Railway Law are not effective enough to be used as a basis as a regulation for transportation responsibilities, because related to the provisions for compensation to consumers, the arrangements are not clear enough. Meanwhile, the responsibility for transportation carried out by PT KAI (Persero) to consumers is based on the Railway Law by adhering to the principle of presumption of guilt (presumption of liability). In addition, in practice PT KAI (Persero) transferred its responsibility to PT Asuransi Jasa Raharja. In fact, between the two there are differences. PT KAI (Persero) is responsible based on the Railway Law while PT Asuransi Jasa Raharja is responsible based on Law Number 33 of 1964 concerning the Mandatory Insurance Fund for Passenger Accidents and Law Number 34 of 1964 concerning the Compulsory Coverage Fund for Road Traffic Accidents. That is clearly unprofitable for consumers. Therefore, if the basic loss element of the claim is not met by the Railway Law, then the consumer can file a lawsuit on the basis of unlawful acts, based on Article 1365 jo Article 1367 of the Civil Code